PENGGUNAAN HANDUK, KEBIASAAN MENGGIGIT KUKU JARI TANGAN TERHADAP KEJADIAN INFEKSI SOIL TRANSMITTED HELMINTH (STH) PADA ANAK PANTI ASUHAN DI JAYAPURA - Hartati, Risda; Simega, Novianti Yoyo; Imbi, Meidy J.; Sahli, Indra Taufik; Asrianto, Asrianto (Politeknik Kesehatan Kemenkes Bengkulu, 2021)
Problem: Helminthiasis is generally caused by the group of Soil Transmitted Helminth (STH) worms, namely Ascaris lumbricoides, Trichuris trichiura and hookworm. Worms have an impact on health problems such as diarrhea, malnutrition and anemia. Risk factors for helminthic infection including poor personal hygiene care, nail biting habits, the habit of not wearing footwear, contact with soil media, will increase the transmission of eggs that inhabit the intestines. The Aim Of The Research: To determine the prevalence of helminthiasis and risk factors for STH intestinal worms in children living in an orphanage in Jayapura. Research Method: Fecal samples were collected from orphanage children (n= 63) using saturated salt solution to detect the presence of STH worm eggs between months August-October 2020. The Results: The prevalence of STH worm infection in orphanages in Jayapura was 12.69% in the highest age group, 6-11 years old with Ascaris lumbricoides, Trichuris trichiura and hookworm infections. The dominant risk factors represented among the most infected children include sharing of towels, the habit of biting fingernails and the habit of not wearing footwear while playing were very significant factors for the incidence of STH worm infection (p<0.05). Conclusion: The prevalence of STH worm infection in orphanage children in Jayapura was 12.69% in the highest age group 6-11 years with the most dominant risk factors are the habit of not wearint footwear while playing, the habit of biting fingernails and sharing towel together.